2017
DOI: 10.1093/nar/gkx1291
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 phosphorylation by ATM downregulates BER and promotes cell elimination in response to persistent DNA damage

Abstract: ATM (ataxia-telangiectasia mutated) is a central molecule for DNA quality control. Its activation by DNA damage promotes cell-cycle delay, which facilitates DNA repair prior to replication. On the other hand, persistent DNA damage has been implicated in ATM-dependent cell death via apoptosis; however, the mechanisms underlying this process remain elusive. Here we find that, in response to persistent DNA strand breaks, ATM phosphorylates transcription factor Sp1 and initiates its degradation. We show that Sp1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Only statistically significant differences are indicated using asterisks decrease in XRCC1 levels. Expression of XRCC1 is controlled by the transcription factor Sp1, and depletion of Sp1 leads to a deficiency in BER due to decreased transcription of XRCC1 [27]. Consistent with this, KD of Sp1 for 72 h led to a significant reduction of XRCC1 protein levels, as well as an increase in pATM, supporting the notion that Sp1 KD leads to persistent DNA damage due to a depletion in XRCC1 protein levels ( Fig.…”
Section: Xrcc1 Kd Imparts Human Fibroblasts With a Survival Advantagesupporting
confidence: 78%
See 1 more Smart Citation
“…Only statistically significant differences are indicated using asterisks decrease in XRCC1 levels. Expression of XRCC1 is controlled by the transcription factor Sp1, and depletion of Sp1 leads to a deficiency in BER due to decreased transcription of XRCC1 [27]. Consistent with this, KD of Sp1 for 72 h led to a significant reduction of XRCC1 protein levels, as well as an increase in pATM, supporting the notion that Sp1 KD leads to persistent DNA damage due to a depletion in XRCC1 protein levels ( Fig.…”
Section: Xrcc1 Kd Imparts Human Fibroblasts With a Survival Advantagesupporting
confidence: 78%
“…This decrease in XRCC1 levels resulted in a lowered BER capacity and led to accumulation of persistent DNA damage. Mechanistically, persistent DNA damage was found to induce ATM-dependent degradation of the transcription factor Sp1, which controls XRCC1 expression, therefore creating a BER deficiency through decreasing transcription of XRCC1 [27]. Thus, somewhat counterintuitive to what would be expected for maintenance of DNA integrity in response to stressful conditions, cellular BER capacity is curbed through downregulation of XRCC1 in response to persistent DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Some cells that accumulate DNA damage eventually die due to late triggering of apoptosis, as observed in colon cells overexpressing GH (32) and evidenced by reduced colony formation in cells treated with both etoposide and GH compared with etoposide alone. P53 phosphorylation and stabilization results in temporal proliferation block to allow cells to repair DNA damage (69,70). We previously showed that GH suppresses total p53 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Fas has been documented as a marker for breast cancer patients with good prognosis, and accumulating studies have demonstrated the involvement of Sp1 and the miR‐146a target, IRAK1, in the progression of HER2‐positive malignancies . Sp1 was reported as a substrate of several kinases with varied functional implications of phosphorylation at different amino acid residues . Thus, further studies are needed to identify the serine/threonine protein kinase that mediates HER2‐elicited phosphorylation of Sp1, and to explore whether other pathways are also capable of phosphorylating Sp1 at the same site.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Sp1 was reported as a substrate of several kinases with varied functional implications of phosphorylation at different amino acid residues. 39,40 Thus, further studies are needed to identify the serine/threonine protein kinase that mediates HER2-elicited phosphorylation of Sp1, and to explore whether other pathways are also capable of phosphorylating Sp1 at the same site. In addition, although our study suggests a critical role of Sp1 in disrupting the expression of tumor suppressors exemplified by MIR146A and FAS, it remains an open issue how this mechanism globally affects the epigenome of HER2-positive breast cancer.…”
Section: Discussionmentioning
confidence: 99%